Needs Analysis of Adobe Flash Media on Akidah Akhlak Subject for Grade 11 Students at MA Muslimat NU Palangka Raya - Aisyah, Siti; Rusma Hidayati (Institut Agama Islam Al-Quran Al-Ittifaqiah (IAIQI) Indralaya, 2024)
The purpose of this study is to identify the strengths and weaknesses that students in the Akidah Akhlak program are taught. Subsequently, we identify the media used in the educational process, recommend media that should be properly developed for the study of Akidah Akhlak, and provide an analysis of the requirements for Adobe Flash media in the study of Akidah Akhlak. One type of research that is used is research and development (R&D) using a 4D model of growth that is adjusted at the stage of development only. In order to gather information, the researchers sent an online questionnaire to the Kelas XI MA Muslimat NU Palangka Raya students via WhatsApp social media. The analytical method used is a deskriptif kualitatif analysis. The results of the survey indicate that the Akidah Akhlak language is widely taught in the learning community because it is perceived as something that students need to understand and have knowledge of. About 80% of teachers use LKS as a popular teaching medium in their classrooms. Additionally, the Akidah Akhlak curriculum contains materials that cause students to become anxious, such as the aliran Kalam. Approximately 27% of students experience difficulty understanding the language used in the material. About 75% of students require Adobe Flash as a learning resource during the course of their studies. Adobe Flash is designed as carefully as possible to enhance students' learning experience and enable them to comprehend the material being taught as well as meet learning objectives